TikTok as a Digital Stage: Enhancing EFL Learners' Speaking Fluency and Confidence among English Department Students of Institut Pendidikan Nusantara Global (IPNG) - Mul Muliadi; Ulpiana Ulpiana (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
The integration of social media into language learning has transformed traditional teaching practices into more interactive and student-centered approaches. One of the most widely used platforms is TikTok, which allows users to create and share short-form videos in creative ways. This study aims to investigate the role of TikTok as a digital stage in enhancing speaking fluency and confidence among English as a Foreign Language (EFL) learners at the English Department of Institut Pendidikan Nusantara Global (IPNG). This research employed a qualitative descriptive design involving 25 students as participants. Data were collected through questionnaires, semi-structured interviews, and classroom observations. The findings indicate that the use of TikTok significantly improves students' speaking fluency, including pronunciation, vocabulary usage, and speech coherence. In addition, students reported increased confidence and reduced speaking anxiety due to the opportunity to rehearse and re-record their performances before sharing them. Furthermore, TikTok enhances students' motivation and engagement by providing an enjoyable and interactive learning environment. However, it should be used as a complementary tool alongside traditional teaching methods to ensure optimal learning outcomes. In conclusion, TikTok serves as an effective digital platform that supports the development of speaking skills and confidence among EFL learners.